A scaling distributed access control model for blockchain-based file storage systems - Hammoud, Obadah; Tarkhanov, Ivan A. (Frontiers in Blockchain, 2025)
Blockchain is considered as one of the popular solutions for decentralized data storage which offers high availability and data immutability due to the use of a specific structure for storing transaction blocks in combination with consensus algorithms. However, the nature of blockchain makes it not suitable for storing big amounts of data, like access control matrices which are typically used by DAC. This research proposes a new access control model based on DAC and RBAC models that is capable of managing access of various users, by storing minimal data in blockchain, and full data off-chain with the help of Merkle trees. A new model was proposed, which allows compressing access control data off-chain, and storing only Merkle root hash on-chain. The article describes DecStore - blockchain-based file storage system and how access control model can be scaled to more than 1,000 users and 1,000 storage objects using a caching mechanism on the users’ side. Experiments were conducted to verify the scaling of the proposed model. Based on the obtained result, it was concluded that the proposed model is applicable to a wide range of systems, including IoT. This model is one of the first to solve the problem of storing large-dimensional DAC RBAC data.